Gastroesophageal Reflux Disease and Erosive-Ulcerative Lesions of the Gastroduodenal Zone in Schoolchildren of Various Ages in Siberia - E. V. Kasparov; T. V. Polivanova; V. A. Vshivkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To study the prevalence of gastroesophageal reflux disease (GERD) and erosive-ulcerative lesions of the gastroduodenal zone and their association among various age groups of Siberian schoolchildren.Material and methods. In order to identify gastrointestinal complaints, a cross-sectional survey of schoolchildren at the age of 7–17 years in the settlements of the Republic of Tyva, Evenkia and Buryatia was conducted. In total, 1535 schoolchildren were examined (7–11 years old — 855 and 12–17 years old — 680 people) in Tyva, 790 (7–11 years old — 333 and 12–17 years old — 457 people) in Buryatia and 1369 (7–11 years old — 633 and 12–17 years old — 736 people) in Evenkia. GERD diagnosis in schoolchildren was based on the presence of heartburn complaints following the worldwide consensus on the GERD definition among the pediatric population. An esophagogastroduodenoscopy (283 children in Tyva, 110 in Buryatia and 205 in Evenkia) was performed by random selection in the age groups of schoolchildren with gastrointestinal complaints in each region.Results. The GERD prevalence among schoolchildren in Siberia was 6.4 %. At the same time, the clinical signs of GERD were mainly noted in schoolchildren of the older age group: at the age of 12–17 years old in 9.4 % of cases, at the age of 7–11 years old in 3.2 % (p = 0.01) of cases. The indicators in the Republic of Tyva were 9.5 %, which is higher than those for schoolchildren in Buryatia (4.1 %; p = 0.01) and Evenkia (4.2 %; p = 0.01). The disease was represented mainly by a non-erosive form. In younger schoolchildren, the non-erosive form of GERD is diagnosed much less frequently and only in Tyva (14.0 %). Erosive esophagitis was diagnosed in 4 cases (0.7 %), 3 of which were in older schoolchildren in Tyva. Erosive-ulcerative diseases of the stomach and duodenum were recorded, to a greater extent, in older children, and largely in Tyva. A more frequent combination of GERD and erosive-ulcerative lesions of the gastroduodenal zone was noted in Tyva, particularly in the older age group.Conclusion. In Siberian schoolchildren, an association of erosive and ulcerative lesions of the mucosa of the gastroduodenal zone with GERD was established, the severity of which has age-related features and is closely related to the region of residence.